Red Light Running at UTHM Intersection, Batu Pahat, Johor - Mat Sani, Nurul Nadia; David Daniel, Basil (Recent Trends in Civil Engineering and Built Environment, 2021)
Violations of red lights running at intersections often steal the attention of the Malaysian public, which could result in road accidents. Although various alternatives have been introduced such as campaigns, education and law enforcement, they are still unable to address this problem. Indirectly, the red light violation at this intersection has contributed to an increase in accidents in Malaysia. Therefore, a study of red light running at the UTHM intersection was conducted to investigate whether these red light running violations occurred during peak or off-peak times and also to determine whether these red light running violations were associated with time and green cycles. The study area was conducted at the UTHM intersection which focused on vehicles that violated red traffic lights by class vehicles such as motorcycles, cars, small trucks and trucks and buses. Video recording methods have been used for the data collection process and analyzed using several formulas such as Descriptive Statistical Analysis, Chi-Squared Contingency Analysis, Two-Sample t-Test and Regression Analysis. The results of this study found that red light running violations often occur during peak hours but still did not obtain solid evidence due to no significant difference between the number of violations during peak hours and outside peak hours at UTHM junction. In conclusion, the installation of automatic cameras is one of the easiest ways to control the occurrence of traffic light violations at the UTHM junction and improvements in the cycle time and green time by certain parties need to be done based on current road capacity to increase safety for road users.